Medieval French interlocutions shifting perspectives on a language in contact - O'Donnell, Thomas; Gilbert, Jane 1964-; Reilly, Brian J. (York Medieval Press, 2024)
Specialists in other languages offer perspectives on the widespread use of French in a range of contexts, from German courtly narratives to biblical exegesis in Hebrew.French came into contact with many other languages in the Middle Ages: not just English, Italian and Latin, but also Arabic, Dutch, German, Greek, Hebrew, Irish, Occitan, Sicilian, Spanish and Welsh. Its movement was impelled by trade, pilgrimage, crusade, migration, colonisation and conquest, and its contact zones included Muslim, Jewish and Christian communities, among others. Writers in these contact zones often expressed themselves and their worlds in French; but other languages and cultural settings could also challenge, reframe or even ignore French-users' prestige and self-understanding.The essays collected here offer cross-disciplinary perspectives on the use of French in the medieval world, moving away from canonical texts, well-known controversies and conventional framings. Whether considering theories of the vernacular in Outremer, Marco Polo and the global Middle Ages, or the literary patronage of aristocrats and urban patricians, their interlocutions throw new light on connected and contested literary cultures in Europe and beyond